Advanced library system : retrieval book availability information and online booking / Azmira Suhani Jailani - Jailani, Azmira Suhani (2006)
This project prepared for the Faculty of Information Technology and Quantitative Science, is an information management of system for Perpustakaan Tun Abdul Razak. The systems provide services like checking availability book, online booking and much more. This system are divided into two category user where there are for student/lecturer and staff/librarian itself. Librarian or staff can login to this website administration to maintain the operation of this website. They can insert, delete, update and maintain all the matters that related to the literature. Prototype of this project shows how the information displays to the system. This system built using Mambo technology and PHP language with Apache as a server platform. Using existing internet technology, the library could improve their services by being able to reach out to user anytime and anywhere.